Nucleotide sequence analysis of the viral envelope protein gene (P32) region of sheep poxvirus from India - RAJAMUTHU, S; PARTHIBAN, M; KUMAR, T M A SENTHIL; ARUNI, WILSON; KUMAR, S SENTHIL (The Indian Journal of Animal Sciences, 2011)
Seven local field strains of sheep poxvirus from different districts of Tamil Nadu, India and vaccine strains were characterized by sequencing studies to find out the marker gene in an attempt to differentiate the field and vaccine strains. The full length viral envelope protein gene (P32) of sheep poxvirus was amplified and sequenced. The sequence studies revealed that the local field strains possessed 100% and 99.31% homology with Ranipet and Roumanian-Fanar vaccine strains respectively. Sheep poxvirus could not be differentiated based on the envelope protein nucleotide sequence level in any field outbreaks. Â